Penunjukan Gubernur oleh Presiden dalam Wacana RUU Daerah Khusus Jakarta: Kontroversi dan Orientasi - Razak, Askari (Universitas Ekasakti, 2023)
The Special Capital Region of Jakarta Bill has generated controversy regarding the proposal to grant the President the authority to appoint the Governor. Despite concerns about conflicting with regional autonomy, this provision is considered crucial for maintaining the stability of the capital. This research aims to analyze the controversy surrounding the mechanism of the President's appointment of the Governor in the bill and formulate an ideal policy orientation to bridge the interests of the central and local governments. A normative method, utilizing legislative and case law approaches, is employed to examine primary, secondary, and tertiary legal materials, qualitatively analyzing the controversy and policy orientation. The study identifies the controversy arising from Article 10, paragraph (1), allowing the President's direct appointment, potentially undermining citizen participation and democratic principles. To balance central and local government interests, policy orientation can refer to Law No. 23 of 2014, involving direct election of the Governor by the people, with additional conditions and recommendations from the central government. Aligning the Governor of Jakarta's term with the President's and establishing a Jakarta Consideration Council involving both central and local government elements ensures checks and balances. Detailed tasks for the Governor regarding the coordination of national development programs in Jakarta, along with incentives and affirmative policies from the central government, support the region's development as the capital.